Applying design to design: demonstrating how to create a human-centered design session interview guide for use with adolescents - Kruger, Macarena; Goldschmidt, Andrea B.; Ortega, Adrian; Wharton, Abigail; Chapa, Danielle A. N.; Stalvey, Erin R.; Rooper, Isabel R.; Obleada, Katrina T.; Miller, Graham C.; Graham, Andrea K. (Frontiers in Digital Health, 2025)
Digital health interventions (DHIs) hold promise for improving the reach of mental health care for adolescents, particularly those from under-resourced communities who may face significant barriers to accessing in-person care. Yet, low engagement and uptake have challenged DHIs’ potency. Human-centered design (HCD) integrates end-users (i.e., future users of the DHI) into iterative design processes, thereby prioritizing their needs and preferences. Clinical scientists are increasingly embracing HCD, but often lack expertise in how to apply these methods in practice. We provide a template for creating a design session interview guide in a needs assessment, which is the first phase in our HCD process to design a DHI for dysregulated eating in adolescents. To create the guide, we first conducted a “needs assessment” within our team to identify important topic areas that required feedback from adolescents (“investigate”). We then consolidated these ideas into structured domains through a brainstorming process (“ideate”), which resulted in an initial draft of a design session guide (“prototype”). Next, we piloted the prototype with members of our team and a technology-savvy adolescent (“evaluate”) to refine it prior to administration with the target audience (“refine and develop”). Our internal needs assessment identified that we needed to learn adolescents’ preferences for technology (e.g., desired features), clinical content (e.g., areas for specialized support), delivery (e.g., coaching), and developmental relevance (e.g., focus on self-regulation). We organized these topics into six domains: dysregulated eating experiences and current help-seeking behaviors, major challenges that impact dysregulated eating, preferred intervention features and skills, preferences for coaching support, the potential role of sensors to assess activity behaviors, and preferred aesthetics and brand. We created relevant prompts within each domain, revised, and reordered them to elicit more comprehensive responses during administration. Next, we practiced administering the guide internally amongst our team, then with a non-participant adolescent volunteer. Using HCD, we created a semi-structured design session interview guide that will be administered in an upcoming needs assessment with adolescents and will continue to evolve as we learn from adolescents. This case example unpacks the process of creating and iterating a design session guide that could be applied across clinical domains.